Rubber gloves for food industry: Risk from contamination of heavy metals - Pinprayoonl, Orawan; Butaek, Kannika (Bulletin of Applied Sciences, 2022)
The risk of heavy metal contamination from using rubber gloves in food industry was evaluated by determination of five heavy metals, namely lead, cadmium, chromium, arsenic and zinc, using extraction technique and followed by inductively couple plasma optical emission spectroscopy (ICP-OES). Twenty one glove samples, including fourteen natural rubber gloves and seven nitrile rubber gloves, were studied. Gloves specimens were extracted in a 4% acetic acid solution at 40 °C for 10 minutes and the extracted solutions were measured for lead, cadmium, chromium, arsenic and zinc contents. The results showed that there were no lead, cadmium, chromium and arsenic in the acetic acid solutions. However, zinc was detected and the average levels were found to be 4 mg/land 2.7 mg/l for natural rubber gloves and nitrile rubber gloves, respectively. According to the WHO, despite a slightly high level of zinc in 5 samples (above WHO's recommendation level of 5.0 mg/l), these zinc levels were considered post no risk for human health. Therefore, the use of both natural rubber gloves and nitrile rubber gloves in food industry in a normal condition at not more than 40 degrees Celsius has a little risk of the heavy metal contamination.